PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI INTEGRASI APLIKASI PERKANTORAN KELAS X TKJT DI SMK MUHAMMADIYAH 1 PADANG - Sari, Enggi Permata; Irsyadunas, Irsyadunas; Junaidi, Satrio (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The 21st century has witnessed a great deal of change in education because of globalisation and technology advancements that make learning more interesting and faster. The purpose of this project is to use the Android platform to develop authentic and realistic learning resources for the integration of office applications in class X at TKJT SMK Muhammadiyah 1 Padang. This kind of RD (Research and Development) project follows the ADDIE methodology (Analysis, Design, Development, Implementation, and Evaluation). The conclusion of the study shows that media experts in the very valid category have a validity level of 89.29%, while materials in the same field have a validity level of 98.81%. Thus, it can be concluded that the practicality test of Androidbased teaching materials based on teacher practicality data is 97.92% with a very practical category, and the validation results of media experts and media material experts for Android-based teaching materials can be said to be "Very Valid". However, 89.38% of student replies were found in the category of highly practical.